The beetle family Carabidae of Costa Rica and Panam : Descriptions of four new genera and six new species with notes on their way of life (Insecta: Coleoptera) - Erwin, Terry L. (Zootaxa, 2004)
A new genus and two new species of Bembidiini, Tachyina, (type localities in parentheses) Tachysbembix sirena Erwin new genus, new species (P.N. Corcovado, Llorona, 20 km N Estaci n Sirena, 1 100 m, 08 37 N 083 42 W, LS 270500,508300) and Tachysbembix wendyporrasae Erwin new genus, new species (Guanacaste, Nandayure, Estero Jabilla, sea level, 10 02 N 085 11 W, LN 199225,395300), two new genera and two new species of Lachnophorini, Pseudophorticus puncticollis new genus, new species (Lim n, Hamburg Farm, Rio Reventazon, Ebene, 100 m, 10 15' N, 083 28' W) and Guatemalteca virgen Erwin new genus, new species (Heredia, 16.0 km SSE La Virgen, 1050 1150 m, 10 16' N, 84 05' W, LN527381,257085), and a new genus and two new species of Lebiini, Agrina, Valeriaaschero flora Erwin new genus, new species (Guanacaste, P.N. Guanacaste, Estaci n Pitilla, Santa Cecilia, 700 m, 10 59' 33" N, 085 25' 46' W, LN330200,380200) and Valeriaaschero nigrita Erwin new genus, new species (Puntarenas, Peninsula de Osa, Rancho Quemado, 200 m, 8 40' 44" N, 83 34' 00" W, LS292500,511000) are diagnosed, described and illustrated. Thus far, all species are known only from Costa Rica except Valeriaaschero flora Erwin which also occurs in northwestern Panam . The bembidiines live at the sea shore; the lachnophorines live amongst leaf litter in lowland or cloud forests; the lebiines are arboreal in lowland forests. This paper validates the names of the new genera and species so that information about them can be made available for enhancing the National Biodiversity Inventory Project of Costa Rica. In addition, the following species described originally in the genera Euphorticus or Lachnophorus are transferred to Pseudophorticus: Pseudophorticus semirufa (Bates) from Lachnophorus (Bates 1878); Pseudophorticus lucidus (Bates) from Lachnophorus (Bates 1883); Pseudophorticus subauratus (Bates) from Euphorticus (Bates 1884), new combinations.